LKPD Berbasis STEAM Berbantuan Permainan Ular Tangga Sebagai Penguatan Kemampuan Literasi Numerasi di Sekolah Dasar - Anisah, Difla Nurul; Purwandari, Ristiana Dyah (Jurnal Didaktika Pendidikan Dasar, 2024)
Education is the main pillar in facing global challenges, but the quality of education in Indonesia, especially in numeracy literacy, is still low. The application of innovative learning approaches by teachers is very necessary. The STEAM approach which is integrated with traditional games in Student Worksheets (LKPD) is an innovative alternative learning approach in phase A of elementary schools. This research aims to develop STEAM (Science, Technology, Engineering, Art and Mathematics) based LKPD with the help of the snakes and ladders game for class II students at SD Negeri Gumelar, Karangkobar District, Banjarnegara Regency. The development of STEAM-based LKPD with the help of the snakes and ladders game uses the Dick & Carey model. Based on the research results, it is known that the STEAM-based LKPD with the snakes and ladders game has a validity of 92.24%, practicality of 92.05%, and effectiveness results based on N-Gain calculations obtained a score of 0.76, which is a score included in the high category so that there has been an increase. Based on the results of data analysis, the students' pretest mean score = 56.63 and posttest = 89.50. There was an increase of 32.87. Noted that [faa1] There was an increase in students' numeracy literacy skills after being given STEAM-based LKPD with the help of the snakes and ladders game. The conclusion of this research is that [faa2] learning with STEAM-based LKPD assisted by the snakes and ladders game can improve the numeracy literacy skills of students at Gumelar State Elementary School.